Research on the Path of New Media Promoting Undergraduates to Inherit Chinese Excellent Traditional Culture - Xiaoyan Zhu, Xinmeng Li (Forest Chemicals Review, 1970)
Through the questionnaire survey, this paper investigates the current situation of undergraduates inheriting Chinese excellent traditional culture in the new media era. Based on the analysis of the survey results, this paper deeply discusses the positive and negative factors of new media on undergraduates inheriting Chinese excellent traditional culture. This paper studies the countermeasures of applying new media to strengthen the inheritance of Chinese excellent traditional culture by undergraduates, and puts forward some ways to realize the flexible use of new media by undergraduates by continuing to improve and consolidate the construction of new media platform, giving full play to the subjective initiative of teachers, constantly innovating the study mode of traditional culture and continuously improving the innovation and inheritance ability of undergraduates, provide a better way to inherit Chinese excellent traditional culture.